2019
DOI: 10.48550/arxiv.1902.07549
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Measurement and Analysis of the Bitcoin Networks: A View from Mining Pools

Abstract: has received much attention from both industry and the academy. Mining pools, the main components of the Bitcoin network, dominate the computing resources and play essential roles in network security and performance aspects. Although many existing measurements of the Bitcoin network are available, little is known about the details of mining pool behaviors (e.g., empty blocks, mining revenue and transaction collection strategies) and their effects on the Bitcoin end users (e.g., transaction fees, transaction de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Most of the recent works on decentralization in blockchain have focused on Bitcoin [3], [4], [6], [12], [19]. These works pointed out that Bitcoin shows a trend towards centralization because of the emergence of mining pools.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the recent works on decentralization in blockchain have focused on Bitcoin [3], [4], [6], [12], [19]. These works pointed out that Bitcoin shows a trend towards centralization because of the emergence of mining pools.…”
Section: Related Workmentioning
confidence: 99%
“…Later, authors in [3] analyzed the mining competitions among mining pools in Bitcoin from the perspective of game theory and proposed that a rational mining pool may get incentivized to launch a block withholding attack to another mining pool. From the perspective of mining pools, authors in [19] tracked more than 1.56 million blocks (including about 257 million historical transactions) and found that a few mining pools was controlling and will keep controlling most of the computing resources of the Bitcoin network. Through the research of a small fraction of the network, authors in [12] found that the nodes connected with the major mining pools occupy higher mining capacity.…”
Section: Related Workmentioning
confidence: 99%
“…However, there are few studies on the decentralization evaluation of the blockchain systems. In particular, the work of [16] presents the measurement of the mining pool for Bitcoin. Although Gencer et al [17] present a measurement study on the decentralization level of Bitcoin and Ethereum, their study only consider several metrics such as network bandwith, mining power and fairness.…”
Section: A Blockchain System Analysismentioning
confidence: 99%
“…However, there are few studies on the decentralization evaluation of different blockchain systems, especially for DPoS-based EOSIO. In the study [33], Wang et al proposed a measurement study for the Bitcoin mining pool. In addition, Gencer et al proposed a measurement study on the decentralization level of the Bitcoin and Ethereum networks [34].…”
Section: A Blockchain Analysismentioning
confidence: 99%